Corrosion Behavior of Biocompatible Stainless Steels in Physiological Medium for Non-Invasive Diagnosis of Small Fiber Neuropathies Applications - Recio-Cortes, F; Recio-Cortes, F (Wiley-VCH Verlag, 2016)
A non-invasive device based on measurements of electrochemical skin conductance can detect small fiber neuropathy, a sweat gland dysfunction implicated in several diseases. The measurement is related to sweat composition and notably to chloride concentration. To optimize the electrode material, in vitro experiments are performed in mimetic sweat solutions. This work reports on the resistance to pitting corrosion of biocompatible stainless steels (AISI 304L, AISI 430, AISI 430T, D2205) in sweat mimicking electrolyte at pH7 with variable chloride concentration, to determine the most sensitive material to sweat composition. AISI 430 is promising due to its high sensitivity to chloride concentration variations. © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.